FORMULASI DAN EVALUASI SEDIAAN PERONA PIPI (Blush on) CREAM DARI EKSTRAK ETANOL BIJI BUAH TERONG BELANDA (Solanum betaceumCav.) SEBAGAI PEWARNA ALAMI - Adiansyah Adiansyah; Eka Margaret Sinaga; Lestari Sitohang (Jurnal Farmanesia, 2019)
Tamarillo contains red anthocyanin pigments which can be used as an alternative natural dye. The purpose of this study was to formulate a blush preparation from Tamarillo (Solanum betaceum) seed extract in the form of a cream and to determine the ethanol extract of Tamarillo(Solanum betaceum) seeds can be used as a natural dye in the formulation of a cream blush preparation. The study used Tamarillo seed extract with concentrations of 3.75%, 5%, 7, 5%. Data analysis used descriptive analysis by presenting the frequency distribution table of each study. The results obtained indicate that all preparations, namely blanks, preparations with concentrations of 3.75%, 5%, and 7.5% have good organoleptic, meet the requirements of the homogeneity test, have good stability during storage, meet the requirements of the smear power test, meet the requirements for skin pH requirements, not irritating to the skin and the most preferred by panelists is a formula with a concentration of 7.5%. The conclusion of this preparation is that the blush preparation from the ethanol extract of the Tamarillo seeds is good and the most preferred is the color of the preparation with a concentration of 7.5%.